Ecological Spirituality Catechesis Based on Shared Christian Praxis for Catholic Youth in Southeast Aceh - Paulus Halek, Bere; Santa Hutabarat, Margareth Santa Hutabarat; Endang Br Sitorus, Elisabeth Endang Br Sitorus; Salomo Silalahi, Bima (Abrahamic Religions: Jurnal Studi Agama-Agama, 2025)
Faced with the deforestation crisis in Southeast Aceh, with the rate of forest loss reaching ±5,000 hectares/year based on KLHK data in 2024, and the phenomenon of ecological faith dissociation among Catholic Youth (OMK), this research develops an ecological catechesis model based on Shared Christian Praxis (SCP). This model is designed to transform OMK into agents of environmental conservation while overcoming the limitations of conventional catechesis, which is monologic and abstract. By applying Martin Heidegger's (1962) hermeneutic phenomenological method, data were collected through in-depth interviews (31 OMK and 14 community and church leaders), participatory observation of ecological catechesis and reforestation activities, and document study in Southeast Aceh (April-June 2025). The findings prove that (1) the SCP model succeeded in increasing the ecological awareness of 72% of OMK participants through spiritual transformation that interpreted “planting trees as a liturgy of life”; (2) the integration of Laudato Si' teachings with the local wisdom of Adat bak Poe Teumeureuhom strengthened context-based ecological identity; and (3) real action commitments were manifested in reforestation participation (80%) and reduction of single-use plastics (65%). Key recommendations include the adoption of an integrated catechesis module, the church and government, and advocacy for an “ecological refugee” policy based on the Vatican document (POCDP). Theologically, this research affirms the ecological crisis as a path of holiness while making a significant contribution to the development of practical theology, particularly in building a participatory, contextual, and action-oriented ecological catechesis paradigm as a manifestation of authentic faith.